1994
DOI: 10.1161/01.cir.90.6.2645
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival of medically treated patients in the Coronary Artery Surgery Study (CASS) Registry.

Abstract: These results contribute to the understanding of the natural history of coronary artery disease and are also of historical interest. The poor survival of patients with three-vessel disease and low ejection fractions continues to emphasize the importance of considering revascularization for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
232
1
24

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 491 publications
(260 citation statements)
references
References 21 publications
3
232
1
24
Order By: Relevance
“…Mortality rates are even higher in patients with severely depressed left ventricular (LV) function. 1 Several studies showed that surgical revascularization can improve the survival and symptoms of heart failure in some patients. 2,3 The potential benefits of revascularization should be balanced, however, with the higher surgical mortality of patients with LV dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates are even higher in patients with severely depressed left ventricular (LV) function. 1 Several studies showed that surgical revascularization can improve the survival and symptoms of heart failure in some patients. 2,3 The potential benefits of revascularization should be balanced, however, with the higher surgical mortality of patients with LV dysfunction.…”
mentioning
confidence: 99%
“…Although existing data suggest that both imaging modalities are useful for predicting the return of contractile function after revascularization, few data are currently available on their potential value for predicting long-term survival. Accordingly, the aims of the present study were (1) to evaluate the potential prognostic value of exercise-redistribution-reinjection thallium scintigraphy and dobutamine echocardiography in patients with LV ischemic dysfunction and (2) to determine whether assessing myocar-dial viability by either means adds independent prognostic information to that provided by baseline clinical, hemodynamic, and angiographic data and by the assessment of myocardial ischemia alone.…”
mentioning
confidence: 99%
“…A similar study by Rumberger et al 23 , correlating coronary artery calcium quantification on ultrafast tomography in hearts at autopsy and its histopathologic quantification, confirmed these data. Angiographic and coronary artery ultrasound studies have also shown that coronary artery calcification correlates with the load of the atherosclerotic plaque [8][9][10] , and the latter, in turn, correlates with the risk for coronary events [5][6] . Several studies in asymptomatic or symptomatic individuals on coronary artery disease have shown a correlation between coronary artery calcification and obstruction of the lumen of the vessel 9,18,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of the coronary deaths and most myocardial infarctions occur in individuals considered at low to intermediate risk, according to clinical and laboratory parameters 3 . Therefore, assessment of subclinical atherosclerosis through imaging techniques may be useful for risk stratification, because evidence exists that the load of the atherosclerotic plaque correlates with the risk of coronary events [5][6] .…”
Section: Distribution Of Coronary Artery Calcium Scores Determined Bymentioning
confidence: 99%
See 1 more Smart Citation